METHODS OF INDICATING AND DESCRIBING INTONATION IN ENGLISH (British Journal of Global Ecology and Sustainable Development, 2025)
The main factors in intonation are variations in the pitch of the voice. Two of the most popular models of intonation are presented in this article, which should be useful for second language teachers and textbook authors for their own research and for creating course material. In the English language, intonation is often accompanied by stress and rhythm to produce meaning. It is also easier for readers to understand recent primary material on the characteristics of intonation, particularly in relation to languages. It is difficult for second language teachers to use the results of intonation research because of this gap between intonation as it is used in instruction and intonation research. In this piece, I discuss the basic subjects covered in current theoretical research as well as the different approaches intonation may take.